Microplastic particles (1-5mm) in soil samples collected in 2019, Northern Germany - Ivy Kaye Harms; Tim Diekötter; Saskia Troegel; Mark Lenz (PANGAEA, 2020)
The study took place in Schleswig-Holstein, Northern Germany, in spring 2019. We have chosen 15 arable fields that are part of the federal soil monitoring scheme by LLUR and as such are representative of the different soil conditions in the region. At each of the 15 study fields, boreholes were placed along the corner points of a square of approximately 40 m edge length. At each of the corner points, three boreholes were drilled down to depths of 10, 20 and 30 cm, respectively. As a consequence, we had 4 x 3 x 3 = 36 sampling units with a wet weight of ~ 200 g soil per unit that integrated over soil depths of 0-10 cm, 10-20 cm and 20-30 cm, respectively, per study site. Each sampling unit was dimensioned with a ruler and stored in an individual glass container. Thus, in this study a total of 540 sampling units with a total of 123.3 kg soil material was inspected for plastic particles between 1 and 5 mm. In the laboratory, the wet soil mass of each sampling unit was quantified and then the soil volume was reduced by wet sieving. To facilitate the sieving, the soil was first soaked in lukewarm tap water in a beaker (1 l) to dissolve loamy aggregates. Aggregates that did not dissolve easily were gently broken down with the fingers and carefully homogenized with a metal whisk. Then the soil was placed on a steel analysis sieve with a mesh size of 1 mm and rinsed under running tap water until only particles of > 1 mm remained. This material was then transferred into glass petri dishes by using a squeeze bottle made of Polyethylene (PE) filled with tap water and a metal spoon. Excess water was removed from the petri dishes with a disposable syringe (PE and Polypropylene (PP)) and an attached injection cannula (outer diameter 0.8 mm; PP and metal). Next, the content of each petri dish was visually examined twice (once by IK Harms and once by S Troegel) for MP under a stereomicroscope with transmitted light and a 133 Trino Zoom (BMS) with two WF 10x/22 mm oculars. All particles that matched the criteria for the proper identification of MP recommended by Hidalgo-Ruz et al. (2012) were picked and individually placed in 96-well micro test plates that were made from Polystyrene (PS).
In: Harms, IK et al. (2020): Amount, distribution and composition of microplastics in typical agricultural soils in Northern Germany [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.924909